Targeting SETDB1 in cancer and immune regulation: Potential therapeutic strategies in cancer - Bo‐Syong Pan; Cheng‐Yu Lin; Gilbert Aaron Lee; Hui‐Kuan Lin (Kaohsiung Journal of Medical Sciences)
Abstract SET domain bifurcated histone lysine methyltransferase 1 (SETDB1/ESET), a pivotal H3K9 methyltransferase, has been extensively studied since its discovery over two decades ago. SETDB1 plays critical roles in immune regulation, including B cell maturation, T‐cell activity modulation, and endogenous retrovirus (ERV) silencing. While essential for normal immune cell function, SETDB1 overexpression in cancer cells disrupts immune responses by suppressing tumor immunogenicity and facilitating immune evasion. This is achieved through the repression of anti‐tumor immune cell production, ERV silencing, and interference with the type I interferon pathway leading to inhibiting immune checkpoint blockade (ICB) efficacy. Beyond its immunological implications, SETDB1 overexpression fosters tumor growth and metastasis via transcriptional silencing of tumor suppressor genes through histone regulation and activating oncogenic signaling by non‐histone regulation. These multifaceted roles make SETDB1 an attractive epigenetic target for novel cancer therapies. This review explores SETDB1's dual function in immune regulation and tumor progression, emphasizing its potential in the development of innovative cancer treatments targeting epigenetic dysregulation and oncogenic signaling.